Long term clinical outcomes of minimally invasive transforaminal interbody fusion (MIS-TLIF) for lumbar spondylolisthesis in a geriatric (>65 years) population: a systematic review and meta-analysis - Kerimbayev, Talgat; Kuanyshbekov, Yerzhan; Akshulakov, Serik; Karibayeva, Indira (Frontiers in Surgery, 2025)
IntroductionThe minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) technique has become a popular and effective option for treating lumbar degenerative spondylolisthesis, especially in elderly patients. This systematic review and meta-analysis is to evaluate the long-term results of MIS-TLIF for patients with degenerative spondylolisthesis.MethodsWe thoroughly reviewed and analyzed studies from databases like PubMed, Web of Science, Scopus, and Google Scholar, covering research published from 2015–2024. We used random-effects models to estimate overall prevalence, and we conducted sensitivity analyses and assessed publication bias to understand the variability in results. All analyses were done using the “meta” and “metafor” packages in RStudio.ResultsAccording to the random-effects model, the pooled standardized mean difference of the VAS back score dynamics at 12 months post-operative in geriatric MIS-TLIF patients was −4.30, 95% CI [−10.02; 1.42]; the VAS leg pain score dynamics at 12 months post-operative was −2.46, 95% CI [−5.61; 0.68]; the ODI score dynamics at 12 months post-operative was −3.01, 95% CI [−6.02; −0.01]. The VAS back pain score dynamics at 24 months post-operative was −1.77, 95% CI [−2.33; −1.21]; the VAS leg pain score dynamics at 24 months post-operative was −2.29, 95% CI [−3.22; −1.37]; and the ODI score dynamics at 24 months post-operative was −1.92, 95% CI [−2.57; −1.27].ConclusionOur study provides compelling evidence supporting the long-term efficacy of MIS-TLIF for managing lumbar spondylolisthesis in geriatric patients. The findings suggest that MIS-TLIF is associated with significant reductions in back and leg pain, as well as improvements in disability scores over 12 months post-operatively. However, these improvements in pain and functional disability decline at 24 months postoperatively, which could be explained by the physiological nature of degenerative changes in the geriatric population.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024538220, PROSPERO (CRD42024538220).